Negara dalam Terminologi Al-Qur’an - Handoko, Agus (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2025)
The Quran does not conceptually define what a state is and what its form should be, but there are several terms in the Quran that can explain the components of a state. There are several terms often associated with the state, such as the word البلد (al-balad) with its various forms of tashrîf (word patterns) from singular to plural forms like البلاد (al-bilâd), or to feminine forms like بلدة (baldah). The Quran also uses the term madînah to refer to a state. Additionally, the Quran uses the term القرية (al-Qaryah) in its singular form and القرى (al-Qurâ) in its plural form. Similarly, the Quran uses the term الدار (al-Dâr) in its singular form and الديار (al-Diyâr) in its plural form. All these terms refer to the concept of a state. A state is an institution that plays a crucial role in human life, responsible for maintaining security, upholding justice, providing legal certainty, and protecting human rights, as well as teaching respect for authority.